Management of gingival cyst of a newborn: a case report with epidemiological data. - Fathimath Fairooz; Yaafiya Saleem; Md Ashif Iqbal (Update Dental College, 2021)
Introduction: Gingival cyst also known as Dental Lamina cyst. They form small nodules or cysts on the alveolar ridge, each up to 2 mm in diameter. They are considered to be due to proliferation of the epithelial rests of Serres but can arise on the lateral aspects of the ridge and the crest. They are considered to be benign lesions which usually are present on the alveolar ridge and are often mistaken as neonatal tooth. Objective: The aim of this case report is to enlist and describe the diagnostic features and management of the gingival cyst of newborn, as these kind of lesions can cause anxiety and fear among the parents. It is important to diagnose these conditions in order to prevent unnecessary surgical interventions and provide adequate care and proper knowledge to the parents. Method: This is a case study of asymptomatic gingival cyst which was present in a newborn at the time of birth on the lower alveolar ridge. Diagnosis of this keratin filled small cystic lesion was made on the basis of clinical history and oral findings. Conclusion: Gingival cyst of infants are transient lesions. No definitive treatment was given but the patient was kept on follow-up for 3 months during which the lesion regressed by itself. Update Dent. Coll. j: 2021; 11 (1): 23-25